PENERAPAN METODE UMMI DALAM PEMBELAJARAN HAFALAN AL-QUR’AN DI SD MUHAMMADIYAH KETAPANG - Iwan Iwan (CV. Adiba Aisha Amira, 2025)
This study was conducted to determine the implementation of the ummi method in memorising the Qur'an at SD Muhammadiyah Ketapang. This study employed a qualitative approach and descriptive method. To collect data, the researcher conducted interviews, observations, and documentation. The results of this study indicate that 1) the Qur'an surah memorised by second-grade students at SD Muhammadiyah Ketapang consist of five short surah, namely: Q.s. An-Nasr, Q.s. Al-Kafirun, Q.s. Al-Kautsar, Q.s. Al-Ma'un, and Q.s. Al-Quraisy. Meanwhile, the Qur'an surah memorised by third-grade students at SD Muhammadiyah Ketapang are Q.s. Al-Fiil, Q.s. Al-Humazah, Q.s. Al-Asr, Q.s. At-Takastur, and Q.s. Al-Qari'ah. 2) The steps for implementing the ummi method in learning to memorise the Qur'an at SD Muhammdiyah Ketapang are, first getting used to it, second the opening, which consists of: greeting, greeting the students, Islamic songs and reading the prayer for learning, followed by the main activity consisting of recitation together using the Ummi method. After that, one of the students is asked to lead the recitation, provided that he or she has memorised all the compulsory surahs, which are then followed by his or her classmates. Third, the activity is closed by reciting the asmaul husna together and the kafaratul majlis prayer. 3) Challenges in implementing the Ummi method in Quran memorisation at SD Muhammadiyah Ketapang include a lack of collaboration among teachers in applying the Ummi method, as well as low motivation among teachers to learn the method due to various commitments and a lack of understanding among students regarding tajwid rules and familiarity with the Arabic alphabet.